Myenglishlab as one of the innovative platform in blending learning - Кушмар, Леся Вікторівна; Колот, Любов Анатоліївна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2019)
The article considers the value of MyEnglishLab as one of the newest tools for blending learning of English by philology students. It is an effective and expedient means of teaching English, aimed at developing communication skills, which allows increasing the individualization of educational activities; optimizing the mastering of language structures and grammatical rules; overcoming the monotony of classes in the formation of speech and communicative competence. The interactive platform is one of the most up-to-date tools for blending learning, combining diverse English learning activities in a variety of formats; provides individual feedback; allows 24/7 to complete tasks; supports different learning styles; provides students with a huge amount of supervised PC-based practices that can be done wherever. It contains lexical, grammatical tasks, tasks for listening and reading, tasks after video watching and listening. The tasks are carried out in three stages: the formation of lexical and grammatical skills; improvement of language skills and their use; development of the ability to use lexical and grammatical knowledge acquired during previous two stages. The platform has options for choosing the number of attempts to perform both tests and training exercises, the duration of exercises. The results are available to the teacher in expanded form (how much time the student spent on each task, the number of attempts and the result for each task), which is an opportunity to control the percentage of correct answers, and, if necessary, assign additional exercises. MyEnglishLab implements main functions: cognitive, developing, training, diagnostic and communicative, and based on the principles of individualization (the ability to work individually) and differentiation (the ability to select and offer the necessary tasks of a certain complexity and quantity and in such a sequence that corresponds to the students’ cognitive abilities, their level of knowledge and abilities).